Fatimid policy towards Andalusia (358 AH-567 AH) - Qassim, Abeer Ahad (Thi Qar Arts Journal, 2024)
The period of expansion of the Fatimid's in Morocco is an important period in the history of the Fatimid state, as the Fatimid's began to think about invading Andalusia from the west and wanted to spread the Imami doctrine there, provided that the Islamic Maghreb was completely subject to them. However, the Umayyad's in Andalusia did not allow the Fatimid's to reach Andalusia, and the caliph was the Umayyad there, Al-Nasir li-Din Allah, and he was a ruler famous for his extreme cruelty. The southern Andalusian borders were strengthened to confront Morocco and protect them from any Fatimid attack. The political conflict between the Fatimid's in Morocco reached its peak in Andalusia, where Abd al-Rahman al-Nasir sought to strengthen the bonds of friendship and alliance with the Byzantines. The importance of this topic lies in the fact that it studies an important historical era in the history of Islam, as it talks about the conflict that occurred between the Muslims themselves, and this conflict was in favor of the Byzantine state that was hostile to Islam and Muslims.